Theoretical Chemistry Accounts New Century Issue - Cramer, Christopher J.; Truhlar, Donald G. (Springer Berlin Heidelberg, 2001)
For the New Century Issue of the journal "Theroretical Chemistry Accounts" the advisory editors identified papers from the first century of theoretical chemistry and discussed their importance for the twentieth century with an eye towards the twenty-first century. Sixty-six such perspectives are published in the New Century Issue. To make this unique collection available to younger scientists for entertaining reading and re-reading of the original publications, the publisher decided to reprint a special edition of the issue